Demographic Security of Kazakhstan – the basis for the development of human capital (Journal of Philosophy Culture and Political Science, 2018)
At the initiative of the President of the Republic of Kazakhstan NA. Nazarbayev, our country is realizing the modernization of public consciousness. Spiritual modernization of society is a multifaceted phenomenon, it is closely connected with many spheres of public life, and also is connected with such important problems as ensuring national security, protecting national interests. The purpose of the research work is to analyze the demographic security of Kazakhstan as the basis for the development of human capital and spiritual revival. Scientific and practical significance of the work - the provision of demographic security of the country occupies a special place among modern political problems, this factor also influences the spiritual revival of Kazakhstan. Because, spiritual revival is taking place in conditions of active internal and external migration of the population. The theoretical and practical significance of the political study of these problems is beyond doubt. The research methodology is based on system, comparative, content and event analyzes. Results and results of the research: identification of problems and features of Kazakhstan’s demography, its relationship with the spiritual modernization of society, scientific results help to develop human capital within the framework of spiritual revival.The value of the research - contributes to the provision of demographic security in Kazakhstan.Key words: spiritual revival, demographic security, migration, human capital.